Optimization of wildlife management in a large game reserve through waterpoints manipulation: A bio-economic analysis - Mwakiwa, Emmanuel; de Boer, Willem F.; Hearne, John W.; Slotow, Rob; van Langevelde, Frank; Peel, Mike; Grant, Cornelia C.; Pretorius, Yolanda; Stigter, Johannes D.; Skidmore, Andrew K.; Heitkönig, Ignas M.A.; de Knegt, Henrik J.; et al. (Journal of environmental management, 2013)
Surface water is one of the constraining resources for herbivore populations in semi-arid regions. Artificial waterpoints are constructed by wildlife managers to supplement natural water supplies, to support herbivore populations. The aim of this paper is to analyse how a landowner may realize his ecological and economic goals by manipulating waterpoints for the management of an elephant population, a water-dependent species in the presence of water-independent species. We develop a theoretical bio-economic framework to analyse the optimization of wildlife management objectives (in this case revenue generation from both consumptive and non-consumptive use and biodiversity conservation), using waterpoint construction as a control variable. The model provides a bio-economic framework for analysing optimization problems where a control has direct effects on one herbivore species but indirect effects on the other. A landowner may be interested only in maximization of profits either from elephant offtake and/or tourism revenue, ignoring the negative effects that could be brought about by elephants to biodiversity. If the landowner does not take the indirect effects of waterpoints into consideration, then the game reserve management, as the authority entrusted with the sustainable management of the game reserve, might use economic instruments such as subsidies or taxes to the landowners to enforce sound waterpoint management. ► When environmental costs are internalized, the optimum stock level of the herbivore is reduced. ► The landowner needs to consider both direct and indirect ecological economic effects of a control tool at his disposal. ► The game reserve management may use economic instruments to enforce sound ecological management of waterpoints by landowners.